The 21st Annual Prostate Cancer Foundation Scientific Retreat report. Issue 11 (20th April 2015) - Miyahira, Andrea K.; Simons, Jonathan W.; Soule, Howard R.
Abstract The 21st Annual Prostate Cancer Foundation (PCF) Scientific Retreat was held from October 23‐25, 2014, in Carlsbad, CA. This event is the world's foremost scientific meeting focusing on prostate cancer and brings together leading basic, translational and clinical researchers in prostate cancer and other diverse disciplines to discuss the newest findings most likely to advance the understanding of prostate cancer and the clinical care of prostate cancer patients. This year's meeting highlighted themes including: (i) research integrity and standards for scientific reproducibility; (ii) prostate cancer disparities; (iii) mechanisms and models of prostate cancer progression and dormancy; (iv) mechanisms of therapeutic resistance; and (v) advancements in precision medicine treatments, treatment models, and predictive and prognostic biomarkers. Prostate 75: 1119–1128, 2015. © 2015 Wiley Periodicals, Inc.